Nutrient Drinking Test as Biomarker in Functional Dyspepsia. (4th July 2021) - Scarpellini, Emidio; Van den Houte, Karen; Schol, Jolien; Huang, I-Hsuan; Colomier, Ester; Carbone, Florencia; Tack, Jan
Abstract : INTRODUCTION: Functional dyspepsia (FD) is a prevalent condition with multifactorial pathophysiology, including impaired gastric accommodation (GA), hypersensitivity to gastric distention, and delayed gastric emptying. Drink tests (DT) have been proposed as a potential biomarker for the presence and severity of gastric sensorimotor dysfunction. Thus, we aimed to summarize the state of knowledge on different DT and their potential as a biomarker for FD. METHODS: A PubMed and MEDLINE search was conducted for English language articles, reviews, meta-analyses, case series, and randomized controlled trials, including also published meeting abstracts. RESULTS: Several DT have been described in literature (e.g., different type of liquid, number of calories used, pace of drinking, and subject's awareness of the amount of liquid drunk). FD patients ingest significantly less volume in the different variants of the tests. The slow nutrient ("satiety drinking") test (SDT) studies show the most consistent separation between health and FD and correlation with GA. However, sensitivity to distention may be correlated with rapid DT. SDTs were used to evaluate the effect of several pharmacological agents, often showing concordance between their effects on GA and tolerated nutrient volume. This correlation was not found mainly for agents with central actions. DISCUSSION: An SDT is a potential diagnostic biomarker in FD, reflecting GA. Additional studies are required to confirm its role as a predictive biomarker for treatment outcome in FD.